The relationship investigating between decision support and departmental agility with the mediating role of departmental learning in bank branches - Li, Y. (Elsevier Ltd, 2022)
Nowadays, companies act in an environment where accelerated change demands them to have adaptable strategies. This research aims to study the relationship between Decision support system and departmental agility with the mediating role of departmental learning. The research method is descriptive-correlational. A sample of 203 people from statistical population of 417 Bank employees was determined based on Morgan table, and questionnaires based on non-random sampling were made available among the statistical population. In this study, departmental Agility is a dependent variable, Decision support system is an independent variable, and departmental Learning is a mediating variable. The content of the questionnaires was obtained in terms of content, and the reliability of the questionnaires was determined by Cronbach's alpha coefficient. Structural equation modeling and Factor analysis were employed for data analysis. The results showed that Decision support system has a meaningful relationship with departmental learning (Coefficient of Determination of 0.558) and departmental agility (CoF of 0.562). Also, the meaningful connection is between departmental agility and departmental learning (CoF of 0.455). Another finding was that departmental learning mediates the relationship between Decision support system and departmental agility (CoF of 0.491). Â© 2021 Elsevier Ltd